A lesson from the Sedyatmo package 4 additional elevated lane toll road project - Tri Prakoso, Endar (2011)

(untitled)
The construction of additional elevated lanes in the Prof. Dr. Ir. Sedyatmo Toll Road (Sedyatmo) on both its north and south sides was a fast track project to provide better accessibility to Jakarta’s International Airport Soekarno-Hatta and vice versa. Sedyatmo designed using pile slab bridge structure. Pile slab bridge is a structure which consists of a reinforced concrete slab in one direction (one way slab) and supported by the pile group system. This structure has been tested for application and suitable for soft soil condition. In the phase of construction Sedyatmo, many factors challenges the Contractor to complete this project on time. Demand of toll road project in Indonesia nowdays is still promising. Challenges in optimizing design, cost and construction method of Sedyatmo should be a lesson learned when dealing with the next future project similar to Sedyatmo. The objectives of this study are to compare the design, cost and construction method of Sedyatmo and to suggest factors should be followed when dealing with the pile slab structure project similar to Sedyatmo. Three designs pile slab of Sedyatmo is Original Design, Propose Design and Review Design. Comparasion analysis are employed to compare these design, cost and construction method respectively. Qualitative analysis on key personnels Sedyatmo is conducted to search suggest factors. The analysis found that among those designs, the most desirable is Review Design. The analysis also suggest that factor construction resources are the most suggest factor which should be followed. It should be noted that the best alternatives found in this study are limited to Sedyatmo. If this lesson used, are applied for other projects, they may not yield the same results. This is mainly due to the uniqueness and circumstances of each project.